Protective and therapeutic potential of ginger (Zingiber officinale) extract and [6]‐gingerol in cancer: A comprehensive review. (16th July 2018) - de Lima, Rosália Maria Tôrres; dos Reis, Antonielly Campinho; de Menezes, Ag‐Anne Pereira Melo; Santos, José Victor de Oliveira; Filho, José Williams Gomes de Oliveira; Ferreira, José Roberto de Oliveira; de Alencar, Marcus Vinícius Oliveira Barros; da Mata, Ana Maria Oliveira Ferreira; Khan, Ishaq N.; Islam, Amirul; Uddin, Shaikh Jamal; Ali, Eunüs S.; et al.
Abstract : Natural dietary agents have attracted considerable attention due to their role in promoting health and reducing the risk of diseases including cancer. Ginger, one of the most ancient known spices, contains bioactive compounds with several health benefits. [6]‐Gingerol constitutes the most pharmacologically active among such compounds. The aim of the present work was to review the literature pertaining to the use of ginger extract and [6]‐gingerol against tumorigenic and oxidative and inflammatory processes associated with cancer, along with the underlying mechanisms of action involved in signaling pathways. This will shed some light on the protective or therapeutic role of ginger derivatives in oxidative and inflammatory regulations during metabolic disturbance and on the antiproliferative and anticancer properties. Data collected from experimental (in vitro or in vivo) and clinical studies discussed in this review indicate that ginger extract and [6]‐gingerol exert their action through important mediators and pathways of cell signaling, including Bax/Bcl2, p38/MAPK, Nrf2, p65/NF‐κB, TNF‐α, ERK1/2, SAPK/JNK, ROS/NF‐κB/COX‐2, caspases‐3, ‐9, and p53. This suggests that ginger derivatives, in the form of an extract or isolated compounds, exhibit relevant antiproliferative, antitumor, invasive, and anti‐inflammatory activities.